(untitled) (Journal of Bangladesh Institute of Planners, 2018)
Bangladesh economy has been growing for the last few years (World Bank, 2018). It has 34th largest GDP across the world (Global Edge, 2017). In 2016, 7.1% GDP growth has made it the 2nd largest growing country in the world (Chowdhury and Hossain, 2019). This GDP growth does not represent the development of all sectors and regions of the country rather a few sectors and regions have the major contribution behind high rate. Though having 45% of the labor force work in agricultural sector, it lies at the bottom of the GDP composition in sectors (Global Edge, 2017). Again, the country’s economy, education, commerce, industry etc. are highly centralized in Dhaka (Siddiqui. K et al. 2016). The study tries to find out the discrepancies in this regard. The study is based on twenty broader regions of Bangladesh and their regional economy. The economy of these regions depends on different industrial sectors. The shares of basic and non-basic industries are also different for these regions. The study has also revealed the strength of different industrial sectors in different regions playing both roles either basic or non-basic. It finds that despite centralization, some regions have potential in some specialized sectors. The study also finds that different economic factors are instrumental for the development of regions and sectors. JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 55-66